ä½¿ç”¨æŒ‡äº‹å—æ•™å¦æ–¹æ³•æé«˜MADRASAH ALIYAH DARUL ULUM é«˜ä¸äºŒå¹´çº§å¦ç”Ÿçš„è®¤å—ä¹‰èƒ½åŠ› - Melati, Della Erlita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The influence or function of the referring word to the learning of Mandarin characters is to explain the meaning of the Chinese characters.